Intestinal transit in rural and urban population of Greece - Manousos, O N; Nicolaou, A; Zografos, A; Trichopoulos, D; Merikas, G (Digestion, 1977)
Intestinal transit times and daily stool weights were measured in 14 residents of Athens and 22 residents of a small village of Greece. Subjects in rural Greece have significantly shorter transit times (38.4 vs 56.8 hr) and heavier daily stools (172 vs 131 g) than those living in Athens. These findings may be attributable to the more refined diet of the urban Greek population and may explain the different incidence of certain bowel diseases in the urban and rural population of Greece.